A Review on Thymol-Based Bioactive Materials for Food Packaging - Guarda-Moraga, A; Galotto-Lopez, M; Rojas-Sepulveda, A; Velasquez, E (Elsevier B.V., 2023)
Strict legislation in developed countries concerning the usage and disposal of many chemicals, during the last few decades, brought industrial innovations based on sustainable green processes and nature-based solutions, eliminating toxic wastes and opening the space for broader implementation of natural bioactive compounds and extracts. Thymol, a natural monoterpene with a broad spectrum of strong biological activities, began to be widely applied in science and industry, including the production of active food packaging materials. In this framework, this article provides a comprehensive review on the use of thymol for active food packaging, summarizing reported technologies and explaining the impact of its addition on the thermal, structural, mechanical, and barrier properties of polymeric films. Moreover, this review analysis effects of films’ physical properties on the release of thymol and revises the strategies to tune the release kinetics. It also provides a critical and comprehensive analysis of the published data on the antimicrobial properties of active films containing thymol. Based on the presented data, knowledge gaps were identified, and possible research trends were discussed. The analysis of the presented technologies showed that supercritical solvent impregnation might overcome the drawbacks of conventional processes, such as high thymol loss and its uneven distribution. The reviewed data indicated that bioactive polymeric materials containing thymol, especially PLA, might have applications in flexible and semirigid packaging because of the improvement of polymer ductility. As a successful strategy of tunning thymol s release kinetics, its inclusion into structures such as cyclodextrins and metal-organic frameworks is identified. Finally, it was shown that the antimicrobial activity of the active food packaging and thymol s diffusivity varied significantly depending on the applied technology, the nature of the polymer, and other added compounds. © 2023 Elsevier B.V.